All-Trans Retinoic Acid Inhibits Human Colorectal Cancer Cells RKO Migration via Downregulating Myosin Light Chain Kinase Expression through MAPK Signaling Pathway. (2nd October 2016) - Zuo, Li; Yang, Xiaoping; Lu, Man; Hu, Ruolei; Zhu, Huaqing; Zhang, Sumei; Zhou, Qing; Chen, Feihu; Gui, Shuyu; Wang, Yuan
ABSTRACT: All-trans-retinoic acid (ATRA) inhibits the invasive and metastatic potentials of various cancer cells. However, the underlying mechanism is unclear. Here, we demonstrate that ATRA inhibited colorectal cancer cells RKO (human colon adenocarcinoma cell) migration by downregulating cell movement and increasing cell adhesion. ATRA inhibited the expression and activation of myosin light chain kinase (MLCK) in RKO cells, while the expression level of MLC phosphatase (MLCP) had no change in RKO cells treated with or without ATRA. The expression and activity of MLC was also inhibited in RKO cells exposed to ATRA. Intriguingly, ATRA increased the expression of occludin messenger RNA (mRNA) and protein and its localization on cell membrane. However, ATRA did not change the expression of zonula occludens 1 (ZO-1), but increased the accumulation of ZO-1 on RKO cells membrane. ML-7, an inhibitor of MLCK, significantly inhibited RKO cell migration. Furthermore, knockdown of endogenous MLCK expression inhibited RKO migration. Mechanistically, we showed that MAPK-specific inhibitor PD98059 enhanced the inhibitory effect of ATRA on RKO migration. In contrast, phorbol 12-myristate 13-acetate (PMA) attenuated the effects of ATRA in RKO cells. Moreover, knocking down endogenous extracellular signal-regulated kinase (ERK) expression inhibited MLCK expression in the RKO cells. In conclusion, ATRA inhibits RKO migration by reducing MLCK expression via extracellular signal-regulated kinase 1/Mitogen-activated protein kinase (ERK1/MAPK) signaling pathway.